Wind turbine charge controller - Noor Ain Izzati, Rahim (2012)
Wind energy is become the world’s fastest growing energy source as it meets the environmental concern on the clean generation of electricity. Nowadays, the available wind turbines are optimized to produce maximum power output under limit of wind speeds. Conversely, universal wind turbine charger is not suitable to be used in certain area cause by the rapidly changed of the wind speeds. Throughout this project, wind turbine will be design carefully, select the appropriate battery and control the charging system by diverting excess power to a dump load (could be anything such as light bulb, water heater and etc). The wind source used in experimental will be replaced by the power supply by varying the voltage and current source to see the charging rate controlled by the wind turbine charge controller. This technique should be able to keep the wind turbine in superior performance and prevent from overcharged. Without a doubt, it is safe and economic to be executed.